2017
DOI: 10.1038/ncomms14286
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal ubiquitin transfer identifies ubiquitination substrates under differential control by the two ubiquitin activating enzymes

Abstract: Protein ubiquitination is mediated sequentially by ubiquitin activating enzyme E1, ubiquitin conjugating enzyme E2 and ubiquitin ligase E3. Uba1 was thought to be the only E1 until the recent identification of Uba6. To differentiate the biological functions of Uba1 and Uba6, we applied an orthogonal ubiquitin transfer (OUT) technology to profile their ubiquitination targets in mammalian cells. By expressing pairs of an engineered ubiquitin and engineered Uba1 or Uba6 that were generated for exclusive interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 52 publications
5
46
0
Order By: Relevance
“…We applied the orthogonal ubiquitin transfer (OUT) technique (Zhao et al ., ) to identify the substrate proteins of CHIP E3 ubiquitin ligase in the cell. The OUT system has been established as an efficient platform to identify the direct ubiquitination targets of an E3 enzyme (Liu et al ., ; Wang et al ., ). OUT is enabled by an engineered UB transfer cascade composed of xE1, xE2, and xE3 enzymes that are free of cross‐reactivities with their native partners (‘x’ designates engineered enzymes orthogonal to native enzymes).…”
Section: Resultsmentioning
confidence: 97%
“…We applied the orthogonal ubiquitin transfer (OUT) technique (Zhao et al ., ) to identify the substrate proteins of CHIP E3 ubiquitin ligase in the cell. The OUT system has been established as an efficient platform to identify the direct ubiquitination targets of an E3 enzyme (Liu et al ., ; Wang et al ., ). OUT is enabled by an engineered UB transfer cascade composed of xE1, xE2, and xE3 enzymes that are free of cross‐reactivities with their native partners (‘x’ designates engineered enzymes orthogonal to native enzymes).…”
Section: Resultsmentioning
confidence: 97%
“…The UB;E1 thioester (";" designates the labile thioester bond) is reactive with the catalytic Cys residue of the E2 enzymes to initiate UB transfer. The human genome encodes two E1s, Uba1 (also known as Ube1) and Uba6, which pair with distinct sets of E2s to direct UB transfer to different pools of substrate proteins, with Uba1 being the E1 responsible for the large majority of cellular ubiquitination (Jin et al, 2007;Liu et al, 2017b). Each E1 has unique functions in cell regulation.…”
Section: A the E1-e2-e3mentioning
confidence: 99%
“…Previous studies identified several targets for UBA6-initiated ubiquitination, such as RGS4, RGS5, UBE3A/E6-AP and Shank3 [ 9 , 10 ]. To better understand the biological roles of the dual E1 ubiquitination system, we recently conducted proteome-wide screens for target proteins of UBA1- and UBA6-initiated ubiquitination, using the Orthogonal UB Transfer (OUT) technology, and demonstrated partially overlapped yet distinct pools of substrates for UBA1 and UBA6 [ 11 ]. This work has provided direct evidence of non-redundant functions of the two E1s, which were suggested previously by biological data.…”
Section: Introductionmentioning
confidence: 99%
“…Those data imply an oncogenic role of UBA1 at least in leukemia, myeloma and colon cancer [ 21 24 ]. Our OUT screens have revealed that pathways associated with UBA6-specific ubiquitination are linked significantly to cell morphogenesis, adhesion, motility, survival and stress responses [ 11 ]. Consistently, UBA6 silencing in mammary epithelial MCF-10A cells results in impaired cell polarity and failed formation of lumen [ 11 ], suggesting a key role of UBA6 in mammary epithelial morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation